1999
DOI: 10.1046/j.1365-201x.1999.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of total and free insulin‐like growth factor‐I and insulin‐like growth factor binding protein‐3 after resistance exercise and training in elderly subjects

Abstract: To investigate the effects of an acute bout of exercise on total and free insulin-like growth factor-I and insulin-like growth factor binding protein-3 plasma concentrations, 32 healthy elderly subjects (67-80 years, 16 men) performed a strength test, which consisted of two sets of 12 repetitions at 12-repetition maximum and four sets of 5 repetitions at 5-repetition maximum for horizontal leg press, seated chest press, and bilateral leg extension movements. Ten out of the 32 subjects served as time controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
2
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 29 publications
7
38
2
7
Order By: Relevance
“…Most IGF-I (∼80%) circulates in a 150-kDa, high-affinity complex, which also contains IGFBP-3 and an acid-labile subunit. Analogous to the present findings, studies have found no change in IGF-I and IGFBP-3 concentrations following 8 (Bermon et al 1999) and 12 weeks (Kraemer et al 1999) of resistance training in a similarly aged population. In contrast, a significant increase in plasma IGF-I concentrations following an acute exercise bout was reported in one of these studies (Bermon et al 1999).…”
Section: Molecular Background Of the Observed In Vivo Muscle Charactesupporting
confidence: 68%
See 1 more Smart Citation
“…Most IGF-I (∼80%) circulates in a 150-kDa, high-affinity complex, which also contains IGFBP-3 and an acid-labile subunit. Analogous to the present findings, studies have found no change in IGF-I and IGFBP-3 concentrations following 8 (Bermon et al 1999) and 12 weeks (Kraemer et al 1999) of resistance training in a similarly aged population. In contrast, a significant increase in plasma IGF-I concentrations following an acute exercise bout was reported in one of these studies (Bermon et al 1999).…”
Section: Molecular Background Of the Observed In Vivo Muscle Charactesupporting
confidence: 68%
“…Analogous to the present findings, studies have found no change in IGF-I and IGFBP-3 concentrations following 8 (Bermon et al 1999) and 12 weeks (Kraemer et al 1999) of resistance training in a similarly aged population. In contrast, a significant increase in plasma IGF-I concentrations following an acute exercise bout was reported in one of these studies (Bermon et al 1999). In endurance training studies, IGFBP-3 has been shown to be independent of IGF-I responses and potentially to have its own biological activity at the level of the cell (Jones and Clemmons 1995).…”
Section: Molecular Background Of the Observed In Vivo Muscle Charactesupporting
confidence: 68%
“…This finding supports the hypothesis that local exercise-induced mobilization of tissue-bound IGF-I stores affects local levels of IGF-I in the exercising muscle. In previous exercise studies, circulating f-IGF-I has been determined in an antecubital vein and has been reported to be increased (51) or unchanged (52). In the present study, the quantity of f-IGF-I released was not sufficient to be detectable in the large pool of t-IGF-I in the circulation.…”
Section: Discussionmentioning
confidence: 54%
“…Effect of exercise on IGF-1 system is one aspect that has been investigated by many researchers [3][4][5][6]. Though, few studies showed concern in studying the response of IGF-1 system to resistance exercise [7,8]. Bermon et al [7] examined the impact of a single session of resistance exercise on the levels of IGF-1 in elderly subjects, and found an increase in IGF-1 concentrations after exercise with no significant change in insulin-like growth factor binding protein-3 (IGFBP3) levels.…”
Section: Introductionmentioning
confidence: 99%